Estimating the impact of trained midwives and upgraded health facilities on institutional delivery rates in Nigeria using a quasi-experimental study design - Grépin, Karen Ann; Chukwuma, Adanna; Holmlund, Marcus; Vera-Hernandez, Marcos; Wang, Qiao; Rosa-Dias, Pedro (BMJ Publishing Group Ltd, 2022)
Studies have shown that demand-side interventions, such as conditional cash transfers and vouchers, can increase the proportion of women giving birth in a health facility in low-income and middle-income countries, but there is limited evidence of the effectiveness of supply-side interventions. We evaluated the impact of the Subsidy Reinvestment and Empowerment Program Maternal and Child Health Project (SURE-PMCH) on rates of institutional delivery and antenatal care. The authors used a differences-in-differences study design that compared changes in rates of institutional delivery and antenatal care in areas that had received additional support through the SURE-PMCH program relative to areas that did not. Data on outcomes were obtained from the 2013 Nigerian Demographic and Health Survey. The authors found that the program significantly increased the proportion of women giving birth in a health facility by approximately 7 percentage points (p=0.069) or approximately 10 percent relative to the baseline after 9 months of implementation. The program, however, did not significantly increase the use of antenatal care. The findings of this study suggest there could be important improvements in institutional delivery rates through greater investment in supply-side interventions.